Acceptability, tolerability, and safety of fecal microbiota transplantation in patients with active ulcerative colitis (AT&S Study). Issue 3 (1st September 2019) - Sood, Ajit; Singh, Arshdeep; Mahajan, Ramit; Midha, Vandana; Mehta, Varun; Gupta, Yogesh Kumar; Narang, Vikram; Kaur, Kirandeep
Abstract: Background and Aim: Fecal microbiota transplantation (FMT) targets gut microbiome dysbiosis and is an emerging therapy for ulcerative colitis (UC). Although initial results with FMT in patients with active UC are encouraging, data regarding its acceptability, tolerability, and safety are scant. Methods: A retrospective analysis of patients with active UC (Mayo clinic score ≥ 4), who received multisession FMT (at weeks 0, 2, 6, 10, 14, 18, and 22) via colonoscopy between June 2016 and June 2018, was performed. Patient acceptability, tolerability, and immediate and long‐term safety of the therapy were assessed. Results: Of the 129 patients with active UC who were offered FMT, 101 patients consented, giving acceptability of 78.3%. Fecal slurry retention time improved with each session (3.27 ± 1.06 h for the first session vs 5.12 ± 0.5 h for the seventh session). Abdominal discomfort, flatulence, abdominal distension, borborygmi, and low‐grade fever (30.8%, 15.9%, 9.8%, 7.9%, and 7.6%, respectively) were the most common post‐procedural short‐term adverse events. Long‐term adverse events included new‐onset urticaria ( n = 2, 4.3%), arthritis/arthralgia ( n = 3, 6.5%), depression ( n = 1, 2.2%), partial sensorineural hearing loss ( n = 1, 2.2%), and allergic bronchitis ( n = 1, 2.2%). Thirteen (12.9%) patients dropped out because of adverse events. Conclusion: Fecal microbiota transplantation appears to be a safe and well‐tolerated procedure, with good acceptability in patients with active UC.